Early mobilization in children with pneumonia in mechanical ventilation: randomized clinical trial - Rodrigo Santiago Barbosa Rocha; Cássia Oliveira Cabral da Paz; Janine Brasil de Araújo Moraes; Letícia de Barros Rocha; Mary Lucy Ferraz Maia Fiuza de Mello; Susan Carolina Diniz de Sales; Guilherme Euzébio Lemes; Paulo Eduardo Santos Avila (Universidade Estadual de Maringá, 2023)
Immobility in the bed of pediatric patients in intensive care units increases the risk of morbidities such as pneumonia, with consequences for autonomic function. Physiotherapy based on physical exercise is part of the rehabilitation process and can modify autonomic function. To compare the effects of two physical therapy protocols, one conventional and the other based on physical exercise, on heart rate variability, length of stay and invasive mechanical ventilation in children with ventilator-associated pneumonia. This is a randomized clinical trial, the volunteers were divided into a control group (submitted to a physiotherapy protocol with only breathing exercises and passive mobilization) and an experimental group (submitted to a physiotherapy protocol based on physical exercise). Patients aged 1 to 8 years, on invasive mechanical ventilation, with pneumonia were included. The rehabilitation protocol took place for 4 consecutive days. The collection of heart rate variability occurred in the pre-protocol period, on the 2nd day, 1 day after the end of the protocol. 25 patients completed the study. There was a reduction in the time of invasive mechanical ventilation in the experimental group (p = 0.01). There was an improvement in the heart rate variability of the experimental group in all indices (p < 0.01). The post-protocol analysis of the groups showed significant values in all variables (p < 0.05). Exercise-based physical therapy protocol improved autonomic heart rate modulation and reduced IMV time in children with ventilator-associated pneumonia.